TOXICITY BIOASSAYS OF FOUR DIFFERENT BOTANICALS AGAINST THE HOUSE HOLD PEST : PERIPLANETA AMERICANA (LINNAEUS) (Journal of Science and Technology, 2016)
Studies were carried out on the toxicity of the powders of four botanicals on Periplaneta ameri- cana. The tested plants include: Parquetina nigrescens, Azadirachta indica, Zanthoxylum zanthoxyloides and Eugenia cariophyllus. Each of the plant materials (PM) was pulverized and then applied to the insects in four different doses. The dosage rates were 25%PM+75% biscuit, 50%PM+50%biscuit, 75%PM +25%biscuit  and  100% PM+0% biscuit. Mortality of insects was monitored and recorded  on daily basis for  three days. Three of the tested plants, that is, P ni- grescens, Z zanthoxyloides and E caryophyllus were very effective as mortality of insects treated with all the doses were significantly different P